Study of Hydrolysis on Pb(ZrxTi1-x)O3 Synthesis Using Zirconium(IV) Nitrate as Precursor and Their Densification Process - Akhmad Al-bari; Rachmat Triandi Tjahjanto; Masruroh Masruroh (Chemistry Department, The University of Brawijaya, 2018)
Pb(ZrxTi1-x)O3 has extensive application in electronic components as a thin layer. The densification layer is controlled by some factor such as precursor composition and heating techniques. Therefore, it is necessary to get simply precursor synthesis from zirconium(IV) nitrate stabilized polyol-acetate. In other hand, hydrolysis factor and the heating rate are affected as well as factor control. The PZT synthesis (55:45) was varied in Rw ratio as comparing water mole and the total mole of metal. The result of Rw = 0, 6, 9, and 12 are coated on silicon substrates and annealed with heating rates variate 1, 5, 10, and 30 °C/min for 650°C. The characterization and analysis were performed with FTIR and a microscope. Furthermore, the thermal dynamic behavior and crystal orientation are observed. The results show PZT synthesis from zirconium(IV) nitrate precurseor and PEG-acetate was stable and that can reproduce. The effect of rising of heating rate causes the dissipating PZT agglomeration, while the addition of water causes the cracking of crystals to become more massive.